Lif Deficiency Leads to Iron Transportation Dysfunction in Ameloblasts. (January 2022) - Fan, L.; Ou, Y.J.; Zhu, Y.X.; Liang, Y.D.; Zhou, Y.; Wang, Y.N.
Leukemia inhibitory factor (LIF), a member of the interleukin 6 family of cytokines, is involved in skeletal metabolism, blastocyst implantation, and stem cell pluripotency maintenance. However, the role of LIF in tooth development needs to be elucidated. The aim of the present study was to investigate the effect of Lif deficiency on tooth development and to elucidate the functions of Lif during tooth development and the underlying mechanisms. First, it was found that the incisors of Lif -knockout mice had a much whiter color than those of wild-type mice. Although there were no structural abnormalities or defective mineralization according to scanning electronic microscopy and computed tomography analysis, 3-dimensional images showed that the length of incisors was shorter in Lif −/− mice. Microhardness and acid resistance assays showed that the hardness and acid resistance of the enamel surface of Lif −/− mice were decreased compared to those of wild-type mice. In Lif −/− mice, whose general iron status was comparable to that of the control mice, the iron content of the incisors was significantly reduced, as confirmed by energy-dispersive X-ray spectroscopy (EDS) and Prussian blue staining. Histological staining showed that the cell length of maturation-stage ameloblasts was shorter in Lif −/− mice. Likewise, decreased expression of Tfrc and Slc40a1, both of which are crucial proteins for iron transportation, was observed in Lif −/− mice and Lif -knockdown ameloblast lineage cell lines, according to quantitative reverse transcription polymerase chain reaction, immunohistochemistry, and Western blot. Moreover, the upregulation of Tfrc and Slc40a1 induced by Lif stimulation was blocked by Stattic, a signal transducer and activator of transcription 3 (Stat3) signaling inhibitor. These results suggest that Lif deficiency inhibits iron transportation in the maturation-stage ameloblasts, and Lif modulates expression of Tfrc and Slc40a1 through the Stat3 signaling pathway during enamel development.